A Correlation between Students’ Rewriting of the Story in Film and Their Vocabulary Mastery - Rohdearni Wati Sipayung; Marhaeni K. D. Matondang (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research is focused on a correlation between students’ rewriting of the story in film and t heir vocabulary mastery at the second grade of SMP Taman Siswa Pematangsiantar. The problem of this study is: ‘Is there any correlation between students’ rewriting of the story in film and their vocabulary mastery?’ The objective of this study are: 1) To examine whether there is  a  significant  correlation  between  students’ rewriting of the story in film and their vocabulary mastery; 2) To  find  out  the  contribution  of  watching  film  in  improving  students’ rewriting of the story in film and their vocabulary mastery.  From the data anlysis it can be concluded that: 1) above it can be concluded that the average score of that students’ rewriting of ¬ the story in film variable (X) is 67, 56 (4054: 60). Six students (10%) get excellent level, 13 students (21,6%) get very good, 13 students (21,6%) get good, 8 students (13,33%) get fair, 11 students (18,33%) get poor and 9 students (15%) get very poor; 2) The average score of the students’ ability in writing recount text is 71, 52 (4291: 60). Five students (8,33%) get excellent level, 11 students (18,33 %) get very good, 20 students ( 33,3 %) get good, 14 students ( 23,3 %) get fair, 7 students ( 11,6 %) get poor and 3 students (5 %) get very poor; 3) There is a significant correlation between students’ rewriting of  the story in film variable (X) and the vocabulary mastery variable (Y). This result is obtained from the computation of the correlation between students’ rewriting of the story in film variable (X) and the vocabulary mastery variable (Y) applied to the sample is 0.338 (from the calculation). The critical value of the Pearson r with the 5 % significant level is 0.211 (From the table of statistical book). It means that the result obtained from the computation is greater than its critical value. Therefore, I conclude that the correlation between the two variables above is highly significant.